2020
DOI: 10.1111/jfpe.13379
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high hydrostatic pressure processing on textural properties and microstructural characterization of fresh‐cut pumpkin (Cucurbita pepo)

Abstract: High hydrostatic pressure (HHP) processing is a burgeoning nonthermal sterilization technology has been industrialized in foreign countries. The purpose of this research was to investigate HHP (100–600 MPa/2 min)‐induced texture and cell microstructural changes of fresh‐cut pumpkins compared with untreated and heated samples. Treatment efficacy was evaluated by texture profile analysis and combinational microscopy techniques, including transmission electron microscope (TEM) and confocal imaging. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
4
11
0
Order By: Relevance
“…Recent developments in hurdle technology involve the introduction of innovative techniques as part of the hurdle sequence [ 97 , 98 ], for example HHP [ 55 , 99 , 100 ], PEF [ 101 , 102 ], UV-C (short-wave ultraviolet) [ 100 , 103 , 104 ], ozone [ 105 ], pulsed light [ 106 ], High Power Ultrasound [ 100 ], natural antioxidants extracted from food waste, etc. In Alzamora et al [ 97 ], an overview of the main emerging “nonthermal” factors is presented, together with their mode of action, potential advantages and disadvantages, and the combined processes (complimentary hurdles), which have been used for fruit preservation.…”
Section: Hurdles Applied In the Preservation And Shelf-life Extension Of Fresh-cut Fruits And Vegetablesmentioning
confidence: 99%
“…Recent developments in hurdle technology involve the introduction of innovative techniques as part of the hurdle sequence [ 97 , 98 ], for example HHP [ 55 , 99 , 100 ], PEF [ 101 , 102 ], UV-C (short-wave ultraviolet) [ 100 , 103 , 104 ], ozone [ 105 ], pulsed light [ 106 ], High Power Ultrasound [ 100 ], natural antioxidants extracted from food waste, etc. In Alzamora et al [ 97 ], an overview of the main emerging “nonthermal” factors is presented, together with their mode of action, potential advantages and disadvantages, and the combined processes (complimentary hurdles), which have been used for fruit preservation.…”
Section: Hurdles Applied In the Preservation And Shelf-life Extension Of Fresh-cut Fruits And Vegetablesmentioning
confidence: 99%
“…Two particular absorbances to determine the DE appeared at 1630–1600 and 1740 cm −1 (Peng et al, 2016). The ring vibration within the α‐linkage between (1,4) galacturonic acid has an absorption peak at 830 cm −1 (Hu et al, 2020). The results showed that the ester carbonyl band (1740 cm −1 ) had a higher absorbance than the carboxylate stretching bands (1639 cm −1 ), which indicated a high methoxyl content (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Color evaluation of fresh-cut potato slice during storage at 4 • C Color determination was conducted on potato slice surface via a colorimeter (NH310, Shenzhen 3NH Technology co., Ltd., Guangdong, China). L * (Lightness, black = 0, white = 100), a * (redness > 0, greenness < 0), and b * (yel-lowness > 0, blueness < 0) were measured in color analysis (Hu, et al, 2020). Total color difference (ΔE * ) was measured with the equation as below,…”
Section: 41mentioning
confidence: 99%